Effect of Seed Pretreatment Methods on Germination and Early Seedling Growth of Senna spectabilis - Erick R Zembele; Elisha S Ngulube (International Journal of Forestry Research)
The objectives of the study were to evaluate the effect of pretreatment methods on germination of Senna spectabilis seed and determine the effect of pretreatment methods on height and root collar diameter growth of Senna spectabilis seedlings. The experimental treatments involved were control; seeds soaked in cold water for 12 h, 24 h, and 48 h; seeds soaked in hot water and allowed to cool for 12 h, 24 h, and 48 h; and nicked seeds using secateurs. The experiment was arranged in a completely randomized design (CRD) with four replications. The data variables assessed were seedling height, root collar diameter, and survival rate. Data were subjected to one-way ANOVA using Minitab software. Results showed that there were significant differences p≤0.05 among treatment means on germination, seedling height, and root collar diameter, while the survival rate was not statistically significant p≥0.05. Nicked seeds and those soaked in hot water and allowed to cool for 12 h had an outstanding performance in terms of germination and seedling growth. It is, therefore, recommended that farmers should be encouraged to use nicked and hot water soaked for 12 h seed in order to achieve high germination and growth efficiencies in their homestead gardens.